Atopic Dermatitis Essential Issues - Pereira, Celso (IntechOpen, 2021)
Atopic dermatitis is a chronic skin condition that has a critical impact on patient quality of life. Recently described pathophysiological aspects and new therapeutic approaches have benefitted greatly the management of patients with this condition. This book presents the most current physiopathogenic evidence in atopic dermatitis. It also examines the scientific rationale of currently available treatments as well as potential new options for managing severe forms of the disease. Written by experts in the field, chapters address some of the most important aspects of atopic dermatitis.